Exploring Factors Affecting Gender Disparities in Enrollment Patterns Within Technical Colleges: A Study Of Motor Vehicle Mechanic Trade In Gombe State - KUMAZHEGE, Stephen Z; UMAR, Hadiza (Research Parks Publishers, 2023)
The study titled